Measurement error consequences, applications and solutions - Binner, Jane M., 1961-; Edgerton, David; Elger, Thomas (Bingley, U.K. : Emerald, 2009)
The conference, 'Measurement Error: Econometrics and Practice' was recently hosted by Aston University and organised jointly by researchers from Aston University and Lund University to highlight the enormous problems caused by measurement error in Economic and Financial data which often go largely unnoticed. Thanks to the sponsorship from Eurostat, a number of distinguished researchers were invited to present keynote lectures. Professor Arnold Zellner from University of Chicago shared his knowledge on measurement error in general; Professor William Barnett from the University of Kansas gave a lecture on implications of measurement error on monetary policy, whilst Dennis Fixler shared his knowledge on how statistical agencies deal with measurement errors. This volume is the result of the selection of high-quality papers presented at the conference and is designed to draw attention to the enormous problem in econometrics of measurement error in data provided by the worlds leading statistical agencies; highlighting consequences of data error and offering solutions to deal with such problems. This volume should appeal to economists, financial analysts and practitioners interested in studying and solving economic problems and building econometric models in everyday operations.
Price errors from thin markets and their corrections : studies based on Taiwan's political futures markets / Shu-Heng Chen, Wei-Shao Wu -- Testing for weak separability / Adrian R. Fleissig, Gerald A. Whitney -- Cointegration analysis under measurement errors / Uwe Hassler, Vladimir Kuzin -- A Monte Carlo study of the necessary and sufficient conditions for weak separability / Per Hjertstrand -- Threshold stock price adjustment / Fredj Jawadi -- Testing utility maximization with measurement errors in the data / Barry E. Jones, David L. Edgerton -- The stock of money and why you should care / Logan J. Kelly -- Distribution dynamics and measurement error / Ole Rummel -- Potential biases in substitution estimates and violations of regularity conditions / Leigh Drake, Adrian R. Fleissig -- Analyzing MSI rules for the USA : extracted from a feedforward neural network / Vincent A. Schmidt, Jane M. Binner -- The information content of inflationary expectations derived from bond prices in Israel / David Elkayam, Alex Ilek -- Measurement error in the national accounts / Dennis Fixler -- Introduction : all the results not fit to print : why measurement error haunts empirical work in macroeconomics / Michael T. Belongia.
Print version record
Keywords: Business & Economics -- Econometrics; Econometrics; Econometrics